Knowledge of AIDS Among the Adolescent Students of Two Selected Colleges of Dhaka City - Shirin, Sonia; Ahmed, Shaila (Ibrahim Medical College Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> This descriptive study was conducted in Dhaka city among 139 adolescent students selected purposively from two colleges (one boy's and another girl's). To asses the level of knowledge on AIDS among them, a semi structured questionnaire was used. The mean age of the respondents was 16.8 ± 0.56 years, and all were unmarried. Of them, 44% were in the Science group. Majority (81.3%) of them lived with their parents. The average monthly family income of the respondents was Tk. 15,053 ± 13,453. Nearly all of them (91.4%) reportedly heard about AIDS primarily from the TV. 90% of the respondents mentioned that major routes of transmission were sexual, blood transfusion and sharing of needles among the drug addicts. Transmission through breast feeding and trans-placental transmission was known to few. Almost none (only 5%) knew that body's immunity is decreased by the AIDS virus. 90% respondents said avoiding of unprotected sex is the way for prevention. The role of screening of blood before transfusion and use of condom as prophylaxis was also mentioned by 64% and 48.9% of the respondents respectively. Thus, the overall findings of the study indicate that around half (56.1%) of the respondent's knowledge on AIDS was average, while 34.5% and 9.4% had poor and good knowledge respectively. Improvement of existing academic health educational programmes with introduction of sex education as well as utilizing the popular medias like TV are important avenues to make our adolescents aware and remain safe from the emerging dangers of AIDS. Ibrahim Med. Coll. J. 2007; 1(2): 5-8 Key Words: HIV/AIDS, adolescents, awareness, Bangladesh doi: 10.3329/imcj.v1i2.2897